Immunolocalisation of ghrelin and obestatin in human testis, seminal vesicles, prostate and spermatozoa. (23rd October 2013) - Moretti, E.; Vindigni, C.; Tripodi, S. A.; Mazzi, L.; Nuti, R.; Figura, N.; Collodel, G.
Summary The role of ghrelin and obestatin in male reproduction has not completely been clarified. We explored ghrelin and obestatin localisation in the male reproductive system. Polyclonal antibodies anti‐ghrelin and anti‐obestatin were used to detect the expression of these hormones in human testis, prostate and seminal vesicles by immunocytochemistry, while in ejaculated and swim up selected spermatozoa by immunofluorescence. Sertoli cells were positive for both peptides and Leydig cells for ghrelin; germ cells were negative for both hormones. Mild signals for ghrelin and obestatin were observed in rete testis; efferent ductules were the most immune reactive region for both peptides. Epididymis was moderately positive for ghrelin; vas deferens and seminal vesicles showed intense obestatin and moderate ghrelin labelling; prostate tissue expressed obestatin alone. Ejaculated and selected spermatozoa were positive for both peptides in different head and tail regions. This study confirms ghrelin localisation in Leydig and Sertoli cells; the finding that ghrelin is expressed in rete testis, epididymis, vas deferens and seminal vesicles is novel, as well as the localisation of obestatin in almost all tracts of the male reproductive system. This research could offer insights for stimulating other studies, particularly on the role of obestatin in sperm physiology, which is still obscure.